A World Without Safe Words: Fifty Shades of Russian Grey - Julie A. Cassiday (Journal of Popular Romance Studies, 2020)
Advertised as “The Russian ‘Fifty Shades of Grey’,” the trilogy of romances by the Alisa Klever adapts erotic BDSM to Vladimir Putin’s Russia. Despite an obvious debt to EL James, Klever’s trilogy is a uniquely Russian work that reflects and comments on its social context. Revolving around a damaged yet forceful hero who demands total erotic obedience from the hyper-feminine Arina Krylova, Klever’s trilogy creates a fictional world in which the domination and submission underlying the gender regime in contemporary Russia become explicit. Klever’s books illustrate the prevalence of a distinctly post-feminist eroticism in Putin’s Russia, in which women like the fictional Krylova represent the ideal Russian citizen, since they display those traits deemed most desirable by Putin’s neonational, neoliberal regime. The substantive changes Klever renders to the Fifty Shades formula include a sadistic subplot—without any corresponding masochism—that fundamentally alters the significance of BDSM, so that it comes to represent all forms of violence done to the individual in contemporary Russia. Klever’s trilogy not only depicts, but more importantly critiques contemporary Russian gender roles, urging its female readers to expand those spaces where they can form community and exercise autonomy.